Introducing Children of Environmental Issue in Sekotong Timur Through Project Based Learning - Dewi, Puspita; Yuliatin, Riyana Rizki; Hadi, Sirojul; Syarifaturrahman, Wahyu Kamil; Latif, Kurniadin Abd; Sujaka, Tomi Tri; Ramandha, Muhammad Eka Putra; Fatimatuzzahra, Fatimatuzzahra (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2022)
Nowadays, the environmental issue is one of the biggest problems worldwide. It is because the climate change deteriorates from time to time; the earth becomes warmer, and pollution polluted the environment. Humans have a pivotal role in changing the earth because they damage the ecosystem by using numerous plastics, throw many of rubbish, and cutting plenty of trees. As a result, climate change and global warming become worse. Consequently, all stakeholders need to take the responsibility to protect the earth. Some groups blame the government; however; environmental issues are the government’s responsibility and all society’s matters, including academicians. This community service activity was conducted in one of the remote areas in Bunbeleng village, East Sekotong district, East Lombok. The Project was held by Relawan Saling Jaga Indonesia (Relasi) funded by Direct Aid Program (DAP) Australian Consulate-General, Bali Indonesia coordinated by Isyatul Mardiah. This project was conducted based on Project-based Learning (PBL). There are five stages in implementing this project: planning the project, monitoring the project, presenting the project, and evaluating the project. The environment topics were elaborated in this community through the PBL. After the program, the students have more knowledge in reducing, recycling, and reusing plastics and green programs with planting trees. The students were very enthusiastic and motivated. The collection of the project was exhibited isn the classroom.